Woleaian Reference Grammar - Sohn, Ho-min (PALI Language Texts-Micronesia, 1975)
A systematic presentation of the overall grammatical structure of Woleaian, spoken in the Caroline Islands. For those who want to learn the language and for linguists who are interested for theoretical purposes.